Developing of an e-learning module of science for form two students / Sharul Imran Wahid - Wahid, Sharul Imran (2004)
E-Leaming or Electronic Learning is the use of computers as a learning resources or media (Hooper, 1975) in varying methods such as online delivery of information, communication and education training. The most familiar example is the computer being used to present frames of information and questions, as with CAI (Computer Aided Instruction) (Hooper, 1975). E-Learning provides a new set of tools that can add value to all the traditional learning modes, classroom experiences and textbook study in form of CD-Rom, traditional computer based training or even online E-learning. This project called "Developing of an E-Learning Module of Science Subject For Form Two Students" is a computer-based application which is operated by CD-Rom that can be installed in a computer system or run from the CD itself which acts as a system that enables the secondary students, namely the form two students to learn Science individually at any time, any pace and also at anywhere with the use of computer. It can be an alternative way or an additional method for the students to leam the subject. The language medium used is English language as it suits with the latest specification of the KBSM (Kurikulum Bersepadu Sekolah Menengah) which just begun in the beginning year of 2004. The development of this project is formulated in accordance to the Sekolah Menengah Kebangsaan Sultan Salahuddin Abdul Aziz Shah with some help from the Science teacher in data collection on what is needed to produce this system. Hopefully the prototype of this system will satisfy the user, which is the students and the teachers.